Recent advances in phosphorylation of hetero-nucleophilic reagents via P–H bond cleavage. (25th April 2023) - Li, Sifeng; Fang, Lijing; Dou, Qian; Wang, Taimin; Cheng, Bin
Abstract: Organophosphorus compounds are prevalent in multidisciplinary realms and their preparation has been attracting great attention of synthetic community. To date, a range of review articles focused on the preparation of organophosphorus derivatives has been published, but the construction of P‒X (X ≠ C) bonds has seldom been summarized. The present overview aims to cover the oxidative cross-coupling of P–H compounds (H-phosphinates, H-phosphites, H-phosphine oxides, and H-phosphines) with hetero-nucleophiles (X–H) containing N, O, S or Se atom. The synthetic methods will be categorized into six types based on the route of acquiring the P‒X compounds. It was found that amines, arylhydrazines, amides, sulfoximines, sulfonyl hydrazides, carbazoles, indoles, azides, imines, imidates, alcohols, phenols, carboxylic acids, thiols, thiophenols, selenols, and selenophenols can be served as suitable coupling partners for the construction of P‒X bonds via distinct oxidative cross-coupling pathways. Graphical abstract: Image 1